Voyageurs, corsaires, caravanistes: Aventures en mer, spectacle dans les ports - Depasquale, Carmen (The Northern Mariner / Le marin du nord, 2005)
The Mediterranean Sea is a beehive of activity with all sorts of ships carrying travellers and provisions. It is a treacherous sea, yet, a greater danger lurks in it throughout the eighteenth century: Berber corsair ships and the galleys of the Knights of St John fight each other relentlessly in the name of Religion. In contrast, the natural port of Malta, described by travellers as "magnificent," is the stage wherein the Grand Master of the Order of St John displays his glory. Diaries, letters, accounts, and archival documents bring to life a past that is often glorious, sometimes sad, but invariably fascinating.